The Effect of Language Training on Immigrants' Economic Integration - Empirical Evidence from France - Alexia Lochmann; Hillel Rapoport; Biagio Speciale (Center for Economic Studies and ifo Institute (CESifo), 2017)
We examine the impact of language training on the economic integration of immigrants in France. The assignment to this training, offered by the French Ministry of the Interior, depends mainly on a precise rule: the training is available when the test score of an initial language exam is below a certain threshold. This eligibility rule creates a discontinuity in the relation between the test result and the variables of interest, which is used to estimate the causal effect of this training, through the method of Regression Discontinuity Design. We find that the number of assigned hours of training significantly increases labor force participation of the treated individuals. The language classes appear to have a larger effect for labor migrants and refugees relative to family migrants, for men and individuals below the median age, and for individuals with higher levels of education. Our estimates suggest that the main channel for the improved labor market participation is the information on job search strategies that immigrants derive from the interaction with their classmates and teachers during classes.
Keywords: J15; J61; J68; 330; immigrants integration; language training; Regression Discontinuity Design